In the Name of Fetal Protection: Why American Prosecutors Pursue Pregnant Drug Users (and Other Countries Don’t) - Fentiman, Linda C. (Columbia Journal of Gender and Law, 2019)
For more than three decades, American prosecutors have been bringing criminal prosecutions against pregnant women based on their use of drugs while pregnant, with charges ranging from child abuse or neglect to murder. Almost all of these women are poor, and the vast majority are also women of color-many with histories of childhood sexual or physical abuse and mental disability. In all but three states-Alabama, Kentucky, and South Carolina-such prosecutions have been declared unconstitutional or the resulting convictions have been overturned. Nonetheless, prosecutions continue to be brought, in what can only be described as a crusade against pregnant women in the name of fetal protection. This Article seeks to answer two questions raised by this crusade. The first question is why-what’s in it for the prosecutors who charge these women, particularly when they know that the prosecution will almost certainly be invalidated? The second question is a more cosmic, macro inquiry-what do these prosecutions tell us about the American criminal justice system when compared to the justice systems of other nations?